Thailand’s Bilateral Response to the 2021 Myanmar Military Coup: Historical Contexts and Evolving Strategies - Narayanan Ganesan (International Quarterly for Asian Studies)
Thailand has pursued its own bilateral policy towards Myanmar, which stands in stark contrast to the Five-Point Consensus policy of the Association of Southeast Asian Nations (ASEAN). The central research question of this article is: Why has Thailand articulated its own independent policy towards Myanmar and what are the motivating factors behind this policy? The methodology is based on published materials on the subject and elite interviews with Bangkok-based academics specialising in Myanmar and national security policymakers. Developments are discussed within a neoclassical realist framework that privileges a state’s internal demands, agency choices, and their interaction in turn with emerging opportunities in the external environment. The findings suggest that Thailand has resorted to bilateralism as part of a time-tested strategy that is consistent with similar previous attempts in 1975 and 1988.